2020
DOI: 10.1002/jcp.30031
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of aqueous humor from cataract patients with retinitis pigmentosa

Abstract: A postcataract surgery complication in patients with retinitis pigmentosa (RP) is lens capsular contraction. To identify potential proteins contributing to this phenomenon, high‐performance liquid chromatography/mass spectrometry‐based proteomic analysis was conducted with aqueous humor samples collected from 11 patients who underwent cataract surgeries, with four patients diagnosed as RP and cataract (RP group) and the other seven with only senile cataract group. The upregulated proteins in the RP group were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The fibrotic reaction of residual LECs associated with ACO [ 101 ] and extracellular matrix (ECM) disorder might together work on CCS's pathogenesis in RP [ 34 , 68 , 123 , 124 ]. Recently, a new potential target of stimulating LEC proliferation, tenascin‐C (TNC), was found in a proteomic analysis of the aqueous humor between senile cataract and RP patients with cataracts to be a candidate protein underlying capsular shrinkage pathogenesis [ 138 ].…”
Section: Complicationsmentioning
confidence: 99%
“…The fibrotic reaction of residual LECs associated with ACO [ 101 ] and extracellular matrix (ECM) disorder might together work on CCS's pathogenesis in RP [ 34 , 68 , 123 , 124 ]. Recently, a new potential target of stimulating LEC proliferation, tenascin‐C (TNC), was found in a proteomic analysis of the aqueous humor between senile cataract and RP patients with cataracts to be a candidate protein underlying capsular shrinkage pathogenesis [ 138 ].…”
Section: Complicationsmentioning
confidence: 99%
“…Aqueous humor mass spectrometry was conducted by Cloud-Seq Biotech (Shanghai, China) with a Q Exactive Orbitrap Mass Spectrometer (Thermo Fisher Scientific). Detailed detection procedure and data analysis were as described in a previous study ( Zhang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…As AH also mediates immune responses and helps modulate ocular cell proliferation, differentiation, and wound healing, it may contribute to the regulation of CEC properties [18][19][20][21]. Nevertheless, most of the studies that have conducted proteomic analysis of AH have focused on glaucoma or retinal disorders [17,[22][23][24][25][26]. Recently, a number of studies have reported that immune response in AH can increase oxidative stress and cause senescence of CECs, leading to CECD or graft failure [27][28][29].…”
Section: Introductionmentioning
confidence: 99%